Reversal of the Pension Reform in Poland - Jakubowski, Sebastian (Socialiniai tyrimai, 2016)
In the past, the Polish pension system was based on a pay-as-you-go rule. On 1 January 1999 Poland introduced a major pension reform in order to improve sustainability of the pension system. The new system consisted of three independent pillars. The first one was and still is public and managed by the Social Insurance Institution. It is obligatory, financed using the pay-as-you-go method, created on the basis of a set contribution but operates on the principle of inter-generational solidarity. The second one was based on the market of private pension funds. It was obligatory, financed through funding, also based on a set contribution but without inter-generational solidarity. The third one was and still is intended to supplement the benefits from the first two ones and therefore participation is voluntary. This pillar is based on various forms of private pension schemes. It is financed through funding, based on a set contribution and without inter-generational solidarity. The pension reform of 1999 led to the creation of the pension market in Poland. The formation of the funded pillar of the Polish pension system based on Open Pension Funds (hereinafter OPF) market enabled the accumulation of substantial long term capital. After the first year of functioning of the market the accumulated pension capital was only 2.25 bn PLN. In just 15 years this sum increased more than hundredfold to reach its peak level in November 2013 (306 bn PLN). The comparison of the total pension assets with GDP shows this rapid growth of the pension market in relation to the size of the Polish economy. At the beginning of the third millennium the pension asset to GDP ratio was just 1,33%. Ten years later it was already 15,65% and at the end of 2013 it was 18,3%. Therefore OPF became an important element and a stimulus for the development of the financial markets in Poland. Until 2008 the Polish reformed pension system with compulsory OPF was perceived as a modern and effective solution to problems in an ageing society. It was the global financial crisis that highlighted the major flaws in the OPF market. Despite a constant inflow of contributions to OPF their net assets shrunk to just 130,87 bn PLN in February 2009. For the first time OPF customers were hit by negative consequences of investment risk connected with capital accumulation in these pension funds. The value of their accounting units – financial instruments sold by OPF and accumulated by OPF members in their individual accounts – fell down sharply. Between October 2007 and February 2009 the value of the weighted average accounting unit fell down from 29,80 PLN to just 22,93 PLN. This triggered pension debates among scientists, politicians and people working for pension market institutions in Poland. The Polish Parliament voted Act on amendment to law on the rules of paying out retirement pensions from the assets accumulated in OPF on 6 December 2013. This legal act introduced several fundamental changes in the funded pillar of the Polish pension system. Firstly, a transfer of assets from OPF to the Social Insurances Institution halved the size of the pension market in Poland. OPF were forced to transfer 51,5% of their accounting units to the Social Security Institution on 3 February 2014. The total value of the transferred assets was 153 151,2 mln PLN. The nominal value of the transferred securities was 146 bn PLN. This included: • 130 bn PLN – Treasury Bills, • 15,6 bn PLN – Highway Bonds, • 200 mln PLN – debt securities guaranteed or backed by the State Treasury or the National Bank of Poland. Debt securities transferred to the Social Security Institution were redeemed by the Ministry of Finances. Partial nationalization of the OPF assets led to a reduction of Polish public debt by 145 bn PLN what constitutes 8,5% of GDP. Nevertheless, given a generous indexation of pension rights in the public part of the pension system, a planned decrease of the retirement age in Poland back to the level of 65 for men and 60 for women, negative demographic trends, this positive fiscal effect is just temporary. Secondly, lifetime capital pension benefits (fthe unded pillar of the pension system) were replaced by joint pension benefits from the first and the second pillar and paid out by the Social Insurances Institution. This coincided with introduction of faster withdrawals of capital from OPF. This process starts ten years before an OPF member reaches the retirement age. Each month 1/120 of accounting units accumulated by this member is transferred to his subaccount with the Social Insurances Institution. This only deepens and speeds up a decrease of the OPF assets. Thirdly, the level of contributions paid to OPF was set at 2,92% of gross earnings. But, what is more important, this contribution became voluntary. Since February 2014 insured citizens are not allowed to choose if they still want to pay part of their pension contributions to OPF. According to Act on amendment to law on the rules of paying out retirement pensions from assets accumulated in OPF article 11 all OPF members between 1 April 1 and 31 July 31 2014 had an opportunity to officially declare their will to continue paying pension contributions to a chosen open pension fund. Since 2016 every four years, between 1 April and 31 July 31 all OPF members will have to formally declare their will to continue paying part of pension contributions to OPF. If the insured citizen does not formally declare his will to continue paying part of his pension contribution to OPF, the whole pension contribution (19,52% of gross earnings) shall be received by the Social Insurances Institution. These three changes started a slow process of informal phasing off of capital part of the pension system in Poland and this means a gradual reversal of the pension reform in Poland.